Diseño de procesos para la gestión lean de proyectos en una empresa del sector industrial en el Perú - Paz Alcazar Aquize, Ximena Paola (2021)
The objective of this work is to design a Project Management System (SGP*) that allows an industrial company to manage and execute successful projects. For this, the conditions and resources of the company were analyzed, and the best project management practices were adapted with the principles of the Lean methodology in a proposal focused on results. The scope of this work includes the design, implementation and validation of a SGP that is composed by the categorization of projects based on their size, with this we proceed to define the processes and documents to be used in the next stages of the project. Each project is divided into 4 main phases: Start, Definition, Execution and Closure. The end of each phase is defined by the approval of its deliverable. It is proposed to implement the SGP 100% by mid-2022 with an incremental benefit of 5% per month on 2021 in relation to the losses of the 10 projects evaluated.